Equitable Law Enforcement for Traffic Offenses : Penegakan Hukum Yang Berkeadilan Terhadap Pelanggaran Lalu Lintas - Fridoliavon Sahata Mangaloi Manik; Rizkan Zulyadi; Serimin Pinem (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Traffic violations are a problem that continues to occur and has an impact on public safety. Specific Background: In Serdang Bedagai Regency, traffic law enforcement efforts still face various challenges, despite having a strong legal basis. Knowledge Gap: However, studies that specifically review the process of equitable law enforcement and the obstacles faced by officials in this area are still limited. Aim: This study aims to analyze the rule of law, the implementation of the enforcement process, and the obstacles faced by traffic law enforcement in Serdang Bedagai Regency. Results: The results show that law enforcement refers to Law No. 22 of 2009 concerning Road Traffic and Transportation, with legal settlement through the Sei Rampah District Court Decision which sentenced violators to two years imprisonment. However, weak enforcement of violations such as not wearing helmets or seat belts is a major obstacle. Novelty: This study provides an empirical picture of the relationship between legal provisions, judicial processes, and the reality of traffic law implementation in the region. Implications: The findings provide a basis for policy makers and police officers to strengthen consistent and equitable traffic law enforcement at the local level. Highlights: Highlights the legal basis and judicial process in traffic law enforcement. Identifies practical enforcement gaps in the field. Emphasizes the need for consistent and fair application of traffic laws. Keywords: Law Enforcement, Justice, Traffic Violation, Legal Process